Can democracy be saved? Participation, deliberation and social movements - della Porta, Donatella (Cambridge, 2013)
"Financial crisis, economic globalization and the strengthening of neoliberal policies present stark challenges to traditional conceptions of representative democracy. Yet, at the same time, new opportunities are emerging that propose alternative visions for the future of democracy.